Pengaruh metode pemuatan karbohidrat pada peningkatan kinerja pelari amatir - Sudirman, Sudirman; Zainuddin, M. Said; Husnul, Darul (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Many runners experience decreased performance and premature fatigue, influenced by various factors, including nutrition. The results of the observations show a high level of fatigue and a need for more performance among runners who are members of the running community in Makassar, especially beginner runners. This research aims to examine the effect of the carbohydrate loading method on improving the performance of the amateur runner community in Makassar. This research used an experimental design involving 60 runners from the amateur runner community in Makassar. Subjects were divided into two groups: an experimental group that applied the carbohydrate loading method and a control group that followed a normal eating pattern. Training to measure runner performance The multistage fitness test (MFT) is the instrument to measure runner performance. Data analysis techniques with t-test (paired sample t-test) to see differences using spss version 20. Data analysis showed significant improvements in performance improvement with the carbohydrate application method. The average performance value increased in the experimental group to 46.18 compared to the control group to 37.21. This increase can be seen from the calculated t-value of 13.75. So, the carbohydrate loading method influences performance. The carbohydrate loading method is an effective strategy for improving the performance of running athletes, especially in the Makassar runner community. With proper application, this method can help runners achieve peak performance, reduce fatigue, and increase efficiency during training and competition.